Cover Feature: Manganese Oxide as an Inorganic Catalyst for the Oxygen Evolution Reaction Studied by X‐Ray Photoelectron and Operando Raman Spectroscopy (ChemCatChem 4/2021). Issue 4 (26th January 2021) - Radinger, Hannes; Connor, Paula; Stark, Robert; Jaegermann, Wolfram; Kaiser, Bernhard
Abstract : The Cover Feature shows the potential‐driven phase transformation of Manganosite (Mn II O) to layered Birnessite (Mn III, IV O2 ) in alkaline media. In their Full Paper, H. Radinger et al.  investigate the structural and chemical evolution of various MnOx  thin films as electrocatalysts for the oxygen evolution reaction by X‐Ray photoelectron and  operando  Raman spectroscopy. The displayed conversion with intercalated water molecules and potassium ions is responsible for the electrochemical performance. Nevertheless, the starting material defines the electrocatalytic activity after an electrochemical activation treatment. More information can be found in the Full Paper by H. Radinger et al.